Simbolisme Dan Makna Kerajaan Seribu Tahun Dalam Teologi Wahyu - Ardianto Dua Asa; Aprianus L Moimau (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This article explores the symbolism and theological significance of the Millennial Kingdom in the context of the Book of Revelation. With a focus on specific texts such as Revelation 20:1-10, the author analyzes how this concept became an integral part of the eschatological vision presented in Revelation. Through the overall approach of Revelation theology, this article delves into the profound meaning of the Millennial Kingdom in the eschatonic Christian understanding. Thus, this article contributes to the understanding of